Maslahat Issue In Islamic Microfinancing: A Study Of Islamic Cooperative And Islamic Rural Bank - Hakim, Nurman; Kartika, Tika; Hidayat, Muhammad Faisal; Zahra, Nadia (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
This paper aims to identify the priority of goals and its strategies on Islamic micro-financing especially at Islamic rural banking and Islamic cooperative. This study uses analytic network process (ANP) as data processing method. The findings are: first, maslahat of people is the most dominant goal on Islamic micro-financing both banking and non-bankingservice providers. Therefore, the most dominant alternative to achieve maslahat is to create empowering programs for needed people effectively. Second, internal strategy is the fittest strategy on Islamic micro-financing both Islamic rural bank and Islamic cooperative. And the alternative strategy to imply the internal strategy is to increase employment performance.